On the Real Effects of Inflation and Relative-Price Variability: Some Empirical Evidence - Blejer, Mario I.; Leiderman, Leonardo (The Review of Economics and Statistics, 1980)
Mario I. Blejer, Leonardo Leiderman, On the Real Effects of Inflation and Relative-Price Variability: Some Empirical Evidence, The Review of Economics and Statistics, Vol. 62, No. 4 (Nov., 1980), pp. 539-544